The mental strategies of elite climbing Sherpas - O'Keeffe, Kate (2016)
In the research that has been conducted on extreme sports focus has been on single psychological skills rather than the combination of skills. Extending this limitation, there has been no previous study examining the psychological skills of elite high altitude climbing Sherpas of the Himalayan region. This research aims to describe and understand the psychological skills of high altitude climbing Sherpas as they tackle Mt. Everest whilst leading and supporting an entire expedition team. It further aims to compare and contrast the psychological skills of the climbing Sherpas with elite athletes performing across other high pressure environments. The study consisted of five Sherpas whom all have attempted to climb Mt. Everest, with four of them summiting between one and ten times. All participants were male and between the ages of 35-40. The study was conducted through semi-structured thematic interviews, via two interviews and a focus group. Questions were developed with reference to the seven skills of the ‘Wheel of Excellence’ (Orlick, 2008) used to measure peak performance in the pursuit of excellence. These skills include; focus, ongoing learning, commitment, mental readiness, positive images, confidence and distraction control. Interviews were conducted through English with the consent forms and interview questions translated into Nepalese as a reference for the Sherpas and translators who were present. The analysis of the data was conducted using both an inductive and deductive approach through coding on qualitative analysis software, Atlas.ti. The interviews and focus group were transcribed and analysed into codes through the process of thematic coding. Pre-formed themes based on the seven components of the Wheel of Excellence were used along with themes constructed from the data. The results indicated that the Sherpas utilize extensive psychological skills whilst climbing Mt. Everest and integrated all aspects of the Wheel of Excellence into their pre-climb, actual climb and post-climb routines. Based on the results, the psychological profile of a high altitude climbing Sherpa was established and adapted from the Wheel of Excellence (Orlick 2008), with belief centred as the core component. This unbreakable belief is the most prominent psychological skill comprising of luck, dreams, rituals, and worshipping routines. From this belief, the Sherpas confidence is developed with them placing the upmost trust in their God in keeping them safe and regulating their arousal in the face of adverse conditions. The remaining psychological components include; mental readiness, evaluation, leadership, teamwork, focus and commitment. These components were mostly data-driven with common psychological skills between the Wheel of Excellence and the adapted wheel for high altitude climbing Sherpas being; focus, mental readiness, commitment, and on-going learning. Data-driven psychological components include; teamwork, leadership, the core component of belief and the facilitating factors of positive thinking and safety. All Sherpas accounted for the importance of the mental component over the physical component and placed an emphasis on their role as a leader and in the safety of their client as taking priority over summiting Mt. Everest. Furthermore, it is clear that as the Sherpas brave the extremities, they face many of the psychological skills necessary for competing across elite sporting environments, however they assure that there is no competition on Everest, you either live, or you die.